User-generated reality enforcement: framing violence against black trans women on a video sharing site - Vähäpassi Valo (My University, 2022)
While some scholars have addressed the common cultural tropes about trans people, the way media might sometimes legitimate violence against trans people, and even take part in forms of violence, has not been analysed. This is what this article sets out to do, through an examination of how a verbal and physical attack against black trans women, videotaped and uploaded on a platform for user-generated entertainment, was framed in a way which repeated the symbolic violence (reality enforcement) already at play in the physical (face-to-face) encounter. The article addresses the way this depiction of real violence, framed as entertainment, and coupled with identity invalidation both legitimizes physical violence and delegitimizes black trans feminine people as victims of violence.
Keywords Digital media, femininity, race, symbolic violence, transgender, trans women, violence